Synthesis and characterization of microencapsulated phase change materials with comb-like acrylic co-polymer shell as thermal energy storage materials. (February 2019) - Ma, Yanhong; Xie, Qifei; Wang, Xinzhong; Lu, Jingzhi
Graphical abstract: Highlights: Micro-PCMs with OC and BS binary cores and comb-like acrylic co -polymer shells. The E wt% of these micro-PCMs range from 24.7 wt% to 86.6 wt%. Micro-PCMs show excellent thermal reliability. After 500 times thermal cycling the heat capacity decreased less than 10 wt%. P(BMA- co -DVB) micro-PCMs th ermal insulation board keep s the temperature fluctuation in 3 °C. Abstract: A series of microencapsulated phase change materials (micro-PCMs) with binary core materials (containing octadecane and butyl stearate) and comb-like acrylic co -polymer shells were prepared. Methyl methacrylate (MMA), butyl methacrylate (BMA), lauryl methacrylate (LMA) and stearyl methacrylate (SMA) were respectively introduced to co -polymerize with divinylbenzene (DVB) to form different microcapsules shells. In this work, the influence of the types of core and shell materials, core shell weight ratios (1/1 and 2/1) on thermal properties of micro-PCMs were studied. The chemical structures of these micro-PCMs were verified by FT-IR and NMR. The morphologies were tested by SEM. In addition, DSC and TGA were used to measure thermal properties and reliabilities. Infrared thermo imager was used to compare thermal insulation property of the wallboards that with or without micro-PCMs. The results indicated that these micro-PCMs had compact surfaces and relatively spherical morphology with diameter ranging from 10 to 80 μm. The microencapsulation efficiency of them ranged from 24.7 wt% to 86.6 wt%. P(BMA- co -DVB) micro-PCMs exhibited excellent thermal reliability that after 500 times thermal cycling test that the heat capacity decreased by less than 5 wt%. Finally, a thermal insulation wallboard was fabricated with synthesized P(BMA- co -DVB) micro-PCMs showed excellent thermal energy storage performance that it can keep the temperature fluctuation within 3 °C.